Multidisciplinary approach to enamel defects in a pediatric patient: A case report - Peña-Barraza, Isabel Del Carmen (2023)
Objective: This case report with a multidisciplinary approach describes the clinical diagnosis and treatment of a male pediatric patient with yellowish-brown stains and pitted teeth associated with type IV hypoplastic amelogenesis imperfecta and dark brown irregular stain associated with dental fluorosis. Case report: The clinical manifestations of these disorders were a source of harassment and bullying by the child’s classmates. The treatment plan involved a pediatric dentist, a restorative dentist and a child psychologist. The focus of the restorative dental treatment was to improve function and esthetics. The teeth affected by amelogenesis were restored with injectable composite resin and the microabrasion technique was used on the enamel affected by fluorosis. The patient and his parents were referred for therapy with a pediatric psychologist because of the bullying suffered. The results showed adequate restoration of the enamel affected by amelogenesis imperfecta; however, microabrasion was not able to eliminate dental fluorosis because of the depth of the lesions. Conclusion: The treatment eliminated tooth sensitivity of the affected teeth and improved his smile. Psychological therapy and parental support were key factors in improving his quality of life, with positive effects on his self-esteem.